2016
DOI: 10.1007/s10068-016-0086-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Allium hookeri root water extracts on inhibition of adipogenesis and GLUT-4 expression in 3T3-L1 adipocytes

Abstract: Anti-adipogenic and antidiabetic activities of root water extracts (ARW) were assessed. Oil Red O staining showed that treatment with ARW caused a dose-dependent reduction in lipid accumulation. ARW was also involved in adipocyte lipolysis via LPL activity, and in the concentration of glycerol in a culture medium. On the basis of the concentration of adipokines following ARW treatment, ARW appeared to inhibit expression of PPAR-γ, to reduce concentrations of leptin and resistin, to increase the concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…AH is mainly used as food supplement and medicinal food. Since, AH is introduced in South Korea, the beneficial effects of AH has been extensively investigated including, anti-oxidant [ 14 – 16 ], anti-inflammatory [ 17 ], anti-microbial [ 18 ], anti-obesity [ 20 ] and anti-diabetic [ 21 – 23 ]. Its beneficial effect is attributed to the sulfur compounds, phenolic compounds, phytosterols and vitamin C of AH [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AH is mainly used as food supplement and medicinal food. Since, AH is introduced in South Korea, the beneficial effects of AH has been extensively investigated including, anti-oxidant [ 14 – 16 ], anti-inflammatory [ 17 ], anti-microbial [ 18 ], anti-obesity [ 20 ] and anti-diabetic [ 21 – 23 ]. Its beneficial effect is attributed to the sulfur compounds, phenolic compounds, phytosterols and vitamin C of AH [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although various biological activities of AH root and leaf have been reported, the underlying mechanisms of AH remain unclear. So far, AH root and leaf showed anti-oxidant [ 14 – 16 ], anti-inflammatory [ 17 ], anti-microbial [ 18 ], improvement of bone health [ 19 ], anti-obesity [ 20 ] and anti-diabetic effects [ 21 – 23 ]. Our previous study reported that water extract of AH leaf or root revealed anti-diabetic effects in the type 2 diabetic db/db mice and in the pancreatic β-cell of streptozotocin (STZ)-induced diabetic rats [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known for sweet, bitter, and spicy tastes and so is called "three-tastes namul" in Korea. It contains high amounts of sulfur compounds with unique flavor (Yang et al, 2016), due to which, it is not appreciated in sensory evaluation when it is used as additives in different foods (Jun et al, 2014).…”
Section: Articlementioning
confidence: 99%
“…Beneficial effects of AH are attributed to a variety of phenols (ferulic acid, gallic acid and cinnamic acid), phytosterols, linoleic acid and organosulfur compounds [13]. AH is known to have biological properties, such as being antioxidant [14,15,16], antimicrobial [17], antidiabetic [18,19,20], anti-obesity [21,22], and anti-inflammatory [23,24,25], as well as hepatoprotective effects [26]. It can also improve bone formation [27], gastritis [28], and immune responses [29].…”
Section: Introductionmentioning
confidence: 99%